Whole‐genome resequencing reveals the pleistocene temporal dynamics of Branchiostoma belcheri and Branchiostoma floridae populations. Issue 15 (20th July 2020) - Bi, Changwei; Lu, Na; Huang, Zhen; Chen, Junyuan; He, Chunpeng; Lu, Zuhong
Abstract: Global climatic fluctuations governed the ancestral demographic histories of species and contributed to place the current population status into a more extensive ecological and evolutionary context. Genetic variations will leave unambiguous signatures in the patterns of intraspecific genetic variation in extant species since the genome of each individual is an imperfect mosaic of the ancestral genomes. Here, we report the genome sequences of 20 Branchiostoma individuals by whole‐genome resequencing strategy. We detected over 140 million genomic variations for each Branchiostoma individual. In particular, we applied the pairwise sequentially Markovian coalescent (PSMC) method to estimate the trajectories of changes in the effective population size ( N e ) of Branchiostoma population during the Pleistocene. We evaluated the threshold of sequencing depth for proper inference of demographic histories using PSMC was ≥25×. The PSMC results highlight the role of historical global climatic fluctuations in the long‐term population dynamics of Branchiostoma . The inferred ancestral N e of the Branchiostoma belcheri populations from Zhanjiang and Xiamen (China) seawaters was different in amplitude before the first (mutation rate = 3 × 10 −9 ) or third glaciation (mutation rate = 9 × 10 −9 ) of the Pleistocene, indicating that the two populations most probably started to evolve in isolation in their respective seas after the first or third glaciation of the Pleistocene. A pronounced population bottleneck coinciding with the last glacial maximum was observed in all Branchiostoma individuals, followed by a population expansion occurred during the late Pleistocene. Species that have experienced long‐term declines may be especially vulnerable to recent anthropogenic activities. Recently, the industrial pollution and the exploitation of sea sand have destroyed the harmonious living environment of amphioxus species. In the future, we need to protect the habitat of Branchiostoma and make full use of these detected genetic variations to facilitate the functional study of Branchiostoma for adaptation to local environments. Abstract : This study reported the genome sequences of twenty Branchiostoma individuals by whole‐genome resequencing strategy and applied the pairwise sequentially Markovian coalescent (PSMC) method to estimate the trajectories of changes in the effective population size ( N e ) of Branchiostoma population during the Pleistocene.